(untitled) (Western Pacific Surveillance and Response, 2021)
Problem: From December 2016 to February 2017, two cases of invasive meningococcal disease and one case of meningococcal conjunctivitis, all serogroup W, occurred in Aboriginal children in the Ceduna region of South Australia. The clustering of cases in time and place met the threshold for a community outbreak. Context: The Ceduna region is a remote part of South Australia, with more than 25% of the population identifying as Aboriginal or Torres Strait Islander. Action: As part of the outbreak response, a community-wide meningococcal vaccination programme against serogroups A, C, W and Y was implemented in a collaboration among different agencies of the South Australia Department for Health and Well-being, Aboriginal health and community services providers, and other local service providers and government agencies. The programme comprised an outbreak vaccination schedule, targeting all people aged 3 2 months residing in the cases’ places of residence or in towns with close links. Outcome: Between March and June 2017, 3383 persons were vaccinated, achieving an estimated coverage of 71–85% of the target population, with 31% (n = 1034) of those vaccinated identifying as Aboriginal or Torres Strait Islander. No local cases of serogroup W occurred during the vaccination programme, but two further cases were notified by the end of 2018. Discussion: The participation of a large number of local and non-health-sector stakeholders in programme planning and implementation, a clear response management structure and high community acceptability were identified as key factors that contributed to the programme achieving high vaccination coverage. The need to develop standard operating procedures for community-based outbreak response interventions to ease logistical challenges was considered an important lesson learnt.